Low-power pulse-width-modulated neuromorphic spiking circuit allowing signed double byte data transfer along a single channel - Banks,DJ; Degenaar,P; Toumazou,C (ELECTRON LETT, 2007)
A new design methodology is presented for outputting digital information from asynchronous analogue circuits, which allows signed frequency encoded signal transfer along a single channel. The circuit outputs data as a series of rate and pulse-width encoded spikes: pulse-width modulation is used to represent vector and pulse frequency modulation is used to represent magnitude symbiotically. This technique can be used to increase the bandwidth of multiplexed neural signals, such as for address event registration, or by using a time-to-first-spike system, to multiplex signals on a single channel. Additionally, feedback has been used to improve the switching speed of current starved inverters, reducing their power consumption by over an order of magnitude.